FEA-based design and parameter optimization study of 6-slot 5-pole PMFSM with field excitation for hybrid electric vehicle - Sulaiman, Erwan (2011)
Permanent magnet flux switching machine (PMFSM) with additional coil excitation has several attractive features compared to interior permanent magnet synchronous machines (IPMSM) conventionally employed in HEVs. The variable flux control capability and robust rotor structure make this machine becoming more attractive to apply for high speed motor drive system coupled with reduction gear. This paper presents an investigation into design possibility and parameter optimization study of 6-slot 5-pole PMFSM with hybrid excitation for traction drives in HEVs. The design target is the motor with maximum power more than 123kW and maximum power density more than 3.5kW/kg. A reduction of permanent magnet material for a given torque requirement and an extension in speed and torque ranges are chosen as the optimization indices. The designed motor enables to keep the same power density in existing IPMSM installed on a commercial SUV-HEV.